2015
DOI: 10.1111/jog.12741
|View full text |Cite
|
Sign up to set email alerts
|

Can different geographic conditions affect the formation of striae gravidarum? A multicentric study

Abstract: To the best of our knowledge, this study is the first to evaluate the effect of environmental factors on SG formation. Moreover, our study group is one of the largest in the published work. Environmental factors can affect the formation of striae gravidarum. Further studies with different ethnic groups are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(33 reference statements)
0
9
0
3
Order By: Relevance
“…Younger mothers are more likely to develop striae and to develop severe striae [ 17 , 21 ]. More recently, geographic location and environmental factors [ 27 ] were found to influence the development of striae, while age was not found to be a predisposing factor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Younger mothers are more likely to develop striae and to develop severe striae [ 17 , 21 ]. More recently, geographic location and environmental factors [ 27 ] were found to influence the development of striae, while age was not found to be a predisposing factor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to other recent studies, the geographic position and environmental factors influence a lot the formation of striae. These studies show a minor influence of the age of the patient [28,29].…”
Section: ключевые слова: стрии кожи этиопатогенез местное лечениеmentioning
confidence: 71%
“…One’s impression of skin status is a determining factor in quality of life. Though striae gravidarum does not impose any life-threatening risk, their ugly-looking appearance may cause stress, decrease self-confidence, create mental problems and make women worried about their husbands losing interest in them, which can lead to psychological problems after delivery (1, 3, 7-9). In the present study, there was not a significant relationship between striae severity and general life quality and skin life quality.…”
Section: Discussionmentioning
confidence: 99%
“…Takimoto et al (2011) showed that 73.8% of women are disgusted by striae during pregnancy (6). Although striae do not endanger the mother and the fetus, they may cause a desire to scratch the region leading to small wounds, induce stress over beauty, decrease self-confidence, and create psychological disorders (7-9). These make primiparous women or those who decide to become pregnant inquire about striae and its prevention measures (1, 10).…”
Section: Introductionmentioning
confidence: 99%